Apakah Perempuan Dayak Muslim tidak Mandiri?: Sebuah Kajian terhadap Etos Kerja Perempuan Dayak Muslim - Ajahari; Mualimin; Aris Sugianto (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Previous studies that have been conducted in relation to women’s work ethics in traditional society seem to inadequately generalize the holistic women’s work ethics of tradional society in general. This article was intended to explain another reality found in Tangkahen Dayak moslem society, Indonesia, that is different from general views telling that women in traditional society are not financially productive, have economics dependency to men, and tend to be lazy. This current study was set as qualitative study by using phenomenological approach. The data were selected through observation, interviews, and documentary study. It was found from the result of study that double role that is played by the women of Tangkahen Dayak Moslem have no impact to their productivity and their household chores. In fact, income those women earned from their work can sustain the economic condition of Tangkahen Dayak Moslem families. Thus, it can be concluded that not all women in traditional society have low work ethics. At this stage, social values and norms that are embedded in a society have major influences on realization of women’s work ethics. The social values and norms embedded in Tangkahen Dayak Moslem were found to be a major factor that is able to support and improve women’s work ethics. Accordingly, the general negative stigma about women’s work ethics in traditional society can be proven wrong by the reality of women’s work ethics in Tangkahen Dayak Moslem society. In other words, negative views about women’s work ethics in traditional society only occured in certain communities and can not be used to generalize all women’s work ethics in general traditional society.